Swamps, Flat Earthers, and Boughs of Holly: “Encountering” the Natural World and the Poetics of Environmental Literacy - Wendy Ryden (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
"Encountering” the Natural World and the Poetics of Environmental Literacy